PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN DALAM RUMAH TANGGA DENGAN STATUS NIKAH SIRI - Yuliyani, Allya Putri; Rasji, Rasji (Universitas Muhammadiyah Ponorogo, 2024)
Siri marriage is a marriage that is carried out under the hand or secretly, the reason someone does a siri marriage is usually because they want to avoid adultery, are pregnant outside of marriage, or the man does not want to register their marriage. As a result of this siri marriage, the marriage can be terminated easily, besides that violence against family members is also very vulnerable because the marriage does not have legal force. However, in some cases there are cases of domestic violence in siri marriages that get protection from the PKDRT Law, this makes legal uncertainty in the enforcement of domestic violence cases in siri marriage couples. Legal clarity is needed to provide protection for victims of domestic violence in a siri marriage without violating or changing the provisions of certain laws. The author's goal is for the community to know the consequences of siri marriage and provide information related to law enforcement in domestic violence cases. The method used by the author is normative legal research, whose main focus is on the study of legal norms or rules. Normative legal research aims to analyze legal rules or regulations as part of an interrelated legal system, and see how these rules relate to legal events that occur, the type of data used in this research is secondary data. Secondary data is data obtained from second sources or secondary sources of the data needed. Secondary data in this study such as decisions, books, journals. The author uses a statutory and case approach. The analytical approach to the law is to analyze the meaning contained and used in the legislation conceptually and examine all laws and regulations related to the legal issues being studied.